Assessing risk factors associated with prevalence of canine gastrointestinal parasitic zoonoses in Andhra Pradesh, India - KURUMADAS, ROJA; CHENNURU, SREEDEVI; KROVVIDI, SUDHAKAR; PATTIPATI, MALAKONDAIAH (The Indian Journal of Animal Sciences, 2020)
Prevalence and risk factors associated with gastrointestinal parasites in dogs from central coastal districts of Andhra Pradesh, India was estimated by coprological examination. On examination of faecal samples of 1,907 dogs by saturated zinc sulphate floatation, sedimentation technique and modified Ziehl-Nielsen staining, an overall prevalence of 52.2% was observed. Single species infections were more common (49.7%) than mixed infections (2.5%). A total of 11 different species were detected. The most prevalent species was Ancylostoma canis followed by Toxocara canis, Cystoisospora ohioensis, Dipylidium caninum, Toxascaris leonina, Capillaria aerophila, Diphyllobothrium latum, Cystoisospora canis, Entamoeba spp., Trichuris vulpis and Cryptosporidium spp. The overall prevalence was high in stray dogs (65.9%). The prevalence of A. caninum (31.6%) was significant in pet dogs. Significant relationship between the season and prevalence of parasites was observed, the infection being more prevalent during rainy season. Binary logistic regression analysis identified age, season and the living condition of dogs and lack of zoonotic awareness of owners as risk factors for different parasitic infection.